The concept of Tritangtu at Tarawangsa music performance in Pasir Biru Village, Rancakalong, Sumedang - Sri Rahayu Ferawati; Aris Setiawan (Fakultas Sastra Universitas Negeri Malang, 2023)
This study aims to reveal the aesthetics of the concept of Tritangtu (the trinity) in the Tarawangsa music performance in Kampung Pasir Biru, Rancakalong, Sumedang. Tarawangsa is a ritual ceremony related to religious magic to honor Keursa Nyai (goddess of fertility). The music in this ritual is not just an accompaniment or ritual compliment but even deeper shows a strong connection with the concept of Tritangtu, namely the world of heaven, the human world, and the underworld. This study uses the ethnographic method, by performing an in-depth recording of the event. The recording is to find out in more detail why Tarawangsa music is played, in what context, and how do people believe in it. In addition, the concept of Tritangtu, belief in three main elements (metacosm, microcosm, and macrocosm) shows a thought of the Rancakalong people about the balance of human life with God and nature. The study results show that the cultural customs of the Pasirbiru community, in general, indicate how this balance is maintained. They believe there will be a significant impact if one of the Tritangtu elements is not fulfilled, and Tarawangsa's music is an essential element in this effort.Konsep Tritangtu pada pertunjukan musik Tarawangsa di Desa Pasir Biru, Rencakalong, SumedangPenelitian ini bertujuan untuk mengungkap estetika konsep Tritangtu (urutan tiga unsur) dalam pertunjukan musik Tarawangsa di Kampung Pasir Biru, Rancakalong, Sumedang. Tarawangsa adalah upacara ritual yang berhubungan dengan ritual keagamaan untuk menghormati Keursa Nyai (dewi kesuburan). Musik dalam ritual ini bukan sekedar pengiring atau pujian ritual, tetapi lebih dalam lagi menunjukkan keterkaitan yang kuat dengan konsep Tritangtu yaitu dunia surga, dunia manusia, dan dunia bawah. Penelitian ini menggunakan metode etnografi, dengan mencatat secara mendalam suatu peristiwa. Pencatatan itu untuk mengetahui lebih detail mengapa musik Tarawangsa dimainkan, dalam konteks apa, dan bagaimana masyarakat mempercayainya. Selain itu, konsep Tritangtu, kepercayaan pada tiga unsur utama (metakosmos, mikrokosmos, dan makrokosmos) menunjukkan pemikiran masyarakat Rancakalong tentang keseimbangan hidup manusia dengan Tuhan dan alam. Hasil kajian menunjukkan bahwa adat budaya masyarakat Pasirbiru secara umum menunjukkan bagaimana keseimbangan itu dijaga. Mereka yakin akan ada dampak yang signifikan jika salah satu unsur Tritangtu tidak terpenuhi, dan musik Tarawangsa menjadi unsur penting dalam upaya tersebut.